Fe + CuSO4 = FeSO4 + Cu
Fe(0) + Cu(+2) + SO4(-2) = Fe(+2) + SO4(-2) + Cu(0)
Fe(0) + Cu(+2) = Fe(+2) + Cu(0)
Zn + CuSO4 = ZnSO4 + Cu
Zn(0) + Cu(+2) + SO4(-2) = Zn(+2) + SO4(-2) + Cu(0)
Zn(0) + Cu(+2) = Zn(+2) + Cu(0)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Fe + CuSO4 = FeSO4 + Cu
Fe(0) + Cu(+2) + SO4(-2) = Fe(+2) + SO4(-2) + Cu(0)
Fe(0) + Cu(+2) = Fe(+2) + Cu(0)
Zn + CuSO4 = ZnSO4 + Cu
Zn(0) + Cu(+2) + SO4(-2) = Zn(+2) + SO4(-2) + Cu(0)
Zn(0) + Cu(+2) = Zn(+2) + Cu(0)